Emergency central aortic repair in acute type A aortic dissection complicated by malperfusion - Barnabo Nampoukime, Kan-paatib; Monteiro Igwenandji, Adeoumi Esperance; Pan, Youmin; Wang, Haihao (Frontiers in Surgery, 2025)
ObjectiveTo assess outcomes of emergency central aortic repair (ECAR) in patients with acute type A aortic dissection (ATAAD) complicated by malperfusion, focusing on in-hospital mortality and long-term survival.MethodsThis retrospective cohort study included 545 ATAAD patients treated surgically at a single center. Patients were stratified into malperfusion (n = 149) and non-malperfusion (n = 396) groups. Preoperative laboratory parameters, intraoperative strategies, and postoperative outcomes were compared. Kaplan–Meier analysis evaluated long-term survival.ResultsPatients with malperfusion presented with significantly higher D-dimer and creatinine levels and more frequent emergency surgery (73.8% vs. 63.9%, P = 0.028). In-hospital mortality was similar between malperfusion and non-malperfusion groups (16.1% vs. 14.1%, P = 0.60), but increased with the number of affected organs: 13.3% (single), 18.4% (double), and 30.8% (triple or more). Cardiac and cerebral malperfusion had the highest mortality (40.0%). At 60 months, survival was significantly lower in malperfusion patients (60% vs. 70%, log-rank P = 0.00035).ConclusionECAR provides acceptable early survival in ATAAD patients with malperfusion. However, multi-organ involvement significantly worsens both in-hospital and long-term outcomes.